Formation of new Words with the Suffix in the Albanian Language Today - Bado, Aida (Richtmann Publishing, 2012)
Always, through the language, we can create new words using different ways each times we feel that it is necessary. A goodway to observe this new creative skill in Albanian language is through its explanatory dictionaries. The explanatory dictionary, in thiscase, serves not only to explain or ranked meanings that have the Albanian language words, but through it we can do also a â€œlinguisticphotographyâ€™ of Albanian language. The â€œlinguistic photographyâ€, in this case, means the reflection of the meanings that a word has(linguistic reality) and the word-formation tools that the Albanian speakers use to create a new word. The object of our study relates,exactly, to the desire to analyze the word-formation with suffix, created after year 1980. To do this we will refer at two Albaniandictionaries: Fjalori i gjuhÃ«s shqipe (2006) and Fjalori i gjuhÃ«s sÃ« sotme shqipe (1980) publications of the Academy of Sciences ofAlbania. From these two dictionaries we have extracted the corpus of words that are includes only in the dictionary of 2006. We havedistinguished only the new words from this lexical corpus, which have entered into Albanian language, these last decades, as formationof words with suffixes.